Redetermination of the crystal structure of bis[N,N′-ethylenebis(acetylacetoniminato)nickel(II)] sodium perchlorate, C24H36ClN4NaNi2O8 - Dey, L.; Rabi, S.; Begum, Z. A.; Takase, T.; Rahman, I. M. M.; Tiekink, Edward R. T. *; Roy, T. G. (De Gruyter Open, 2021)
C24H36ClN4NaNi2O8, monoclinic, C2/c (no. 15), a = 19.5909(11) Å, b = 10.8023(6) Å, c = 14.5722(8) Å, β = 112.032(1)°, V = 2858.7(3) Å3, Z = 4, Rgt(F) = 0.0260, wRref(F2) = 0.0701, T = 93(2) K.